Haemodynamic changes induced by submaximal exercise before a dive and its consequences on bubble formation. Issue 6 (30th November 2006) - Blatteau, Jean-Eric; Boussuges, Alain; Gempp, Emmanuel; Pontier, Jean-Michel; Castagna, Olivier; Robinet, Claude; Galland, Francois-Michel; Bourdon, Lionel
Abstract : Objectives: To evaluate the effects of a submaximal exercise performed 2 h before a simulated dive on bubble formation and to observe the haemodynamic changes and their influence on bubble formation. Participants and methods: 16 trained divers were compressed in a hyperbaric chamber to 400 kPa for 30 min and decompressed at a rate of 100 kPa/min with a 9 min stop at 130 kPa (French Navy MN90 procedure). Each diver performed two dives 3 days apart, one without exercise and one with exercise before the dive. All participants performed a 40 min constant-load submaximal and calibrated exercise, which consisted of outdoor running 2 h before the dive. Circulating bubbles were detected with a precordial Doppler at 30, 60 and 90 min after surfacing. Haemodynamic changes were evaluated with Doppler echocardiography. Results: A single bout of strenuous exercise 2 h before a simulated dive significantly reduced circulating bubbles. Post-exercise hypotension (PEH) was observed after exercise with reductions in diastolic and mean blood pressure (DBP and MBP), but total peripheral resistance was unchanged. Stroke volume was reduced, whereas cardiac output was unchanged. Simulated diving caused a similar reduction in cardiac output independent of pre-dive exercise, suggesting that pre-dive exercise only changed DBP and MBP caused by reduced stroke volume. Conclusion: A single bout of strenuous exercise 2 h before a dive significantly reduced the number of bubbles in the right heart of divers and protected them from decompression sickness. Declining stroke volume and moderate dehydration induced by a pre-dive exercise might influence inert gas load and bubble formation.